Examining the adequacy of South African off-exchange equity securities trading regulation - Bisagaya, Andrew (Department of Commercial Law, 2018)
The recent years have seen the recognition of Multilateral Trading Facilities and Alternative Trading avenues in the American and European stock markets. This was required as the markets had grown and regulators were left perpetually behind their needs. This paper looks at whether South Africa has any such facilities/avenues and whether they are adequately regulated. These facilities/avenues allow investors to trade in equity securities away from the exchange on which they are listed. With their increased use however, there are policy concerns that arise that revolve around; price discovery, investor protection, market fragmentation, fair competition and access. It is these concerns that regulators aim to address. The law in South Africa is clear that there are no other legally recognised avenues to trade listed equity securities other than on the exchange on which they are listed. The equities market in South Africa is also comparatively smaller compared to its international counterparts, therefore it is difficult to assess whether there are persons in the business of providing an infrastructure for trading listed securities away from the exchange. Furthermore, they would be doing so illegally thus making monitoring it harder. This paper analyses the laws in the United States and the United Kingdom and uses the work of various authors to examine the policy concerns that arise with the increased use of these trading avenues and how these concerns were addressed. Finally, the paper proposes that the South African regulators should make changes in line with the international counterparts as the market grows.